The impact of new regulations on earnings quality among Malaysian firms - Abdullah, Shamsul Nahar; Che A Halim, Nur Fajrina; Puat Nelson, Sherliza (International Islamic University Malaysia, 2014)
The main purpose of this study is to examine the impact of the establishment of the Audit Oversight Board (AOB) on audit effort and the effect of the introduction of provisions 317A and 320A of the Capital Markets and Services Act (CMSA) and earnings management. Specifically, it is argued that the monitoring role of the AOB leads to auditors being more rigorous in conducting audits so as to achieve high compliance with auditing standards. Thus, auditors have to put in more effort, which requires them to increase audit fees to compensate the increase in hours spent on an engagement. This study hypothesizes that an increase in audit effort should mitigate earnings management due to consequent higher detection of earnings management. As for Sections 317A and 320A of the CMSA, the objective is to ensure the independent directors are more effective in discharging their monitoring roles. It is also hypothesized that the level of earnings management should be reduced as a result of the more effective monitoring by independent boards of directors and audit committees. The data sample comprises 2,124 observations collected from the annual reports of 708 firms for three years from 2009–2011, which covers the periods before and after the establishment of the AOB. The results indicate that there is an increase in audit effort from pre- to post-AOB. This suggests that the monitoring role of the AOB makes auditors more proper in carrying out the audit process and in collating supporting documentation. The regression analyses reveal the role of board independence in reducing earnings management after the new regime was enforced. This study contributes to the corporate governance literature by examining the effect on financial reporting quality after the changes in rules and legislation, especially in respect of the audit regulatory system with the establishment of the AOB and the issuance of Sections 317A and 320A of the CMSA.